Microbial phosphorus and exchange in oxisol with add of suine sludge on maize no-tillage - Mariotto, James Rodrigo; Klauberg Filho, Osmar; Cardoso, Isabel Cristina Mendonça; Neves, Anelize Nunes; Miquelluti, David José (Revista de Ciências Agroveterinárias, 2014)
The use of organic fertilizers like pig slurry promotes the input of significant amounts of P available to plants and microbial biomass, leading to a decrease on P adsorption. This work aimed to evaluate the effect of pig slurry application in crescent rates on the dynamic of microbian phosphorus, anion membrane exchange and Mehlich I. Pig slurry (0, 25, 50, 100 and 200 m3 ha-1) was applied on a Brazilian Oxisol. At 0; 5; 14; 22; 36 and 61 days after application the soil was collected (0-10 cm) evaluating P-microbiotic, anion exchange resin and P-Mehlich. The contrasts used were: C1 = 6T1 - T2 - T3 - T4 - T5 - T6 - T7; C2 = T6 - T7; C3 = T7 - T2; C4 = T2 - T3; C5 = T3 - T4 e C6 = T4 - T5 at treatments in the reading moments and the contrasts to: C1 = 5 daa - 14 daa; C2 = 14 daa - 22 daa; C3 = 22 daa - 36 daa e C4 = 36 daa - 61 daa, at moments in the treatments), tested by “t” student test (p<0,05). Data showed that there was a difference between the treatments P-mic, P-RTA and P-Mehlich, ranging from 1.80 at 22.59 mg kg-1 to P-mic, 0.30 at 102.00 mg kg-1 to P-RTA and 0.94 at 52.31 mg kg-1 to P-Mehlich. On average 43.24; 51.55; 51.22; 121.23 e 360.57% of the P-RTA was incorporated by microbial biomass in time, 5, 14, 22, 36 e 61 daa, respectively.